Application of the complex of actions to increase stress resistance of sports horses - Кабасова, І. О. (Scientific Progress & Innovations, 2018)
In this work studies have been conducted to improve the training system and preparation of horses for competitions, taking into account the stress-stability factor in order to more objective assessment of the working qualities of horses and conducting a better selection of the best animals in breeding on the main selection criterion – ability to work. A set of measures was developed to increase the stress resistance during demonstrations and competitions, aimed at gradually adapting horses to stressors. For conducting experiments, 10 heads of horses of the jumping group of Dergachiv Children and Youth Equestrian Sports School, who had the experience of participating in the competition to overcome obstacles, were selected. The average age of horses was 8.2 years. Research of the types of HND of horses was carried out according to the methodical recommendations of VNIII horse breeding. Assessment of the stress resistance of horses during demonstrative performances was carried out according to the methodology developed by us. Based on the results of the participation of horses in competitions, taking into account the types of higher nervous activity and sex-age indicators, we have formed two equivalent groups of horses – control and experimental, with five horses in each. A set of measures for increasing stress resistance was introduced into the training system of horses of the experimental group from the beginning of the preparatory period in December 2016. During the research, it was found that the application of the developed set of measures has a positive effect on the horses of strong, balanced inert and severe unbalanced types of higher nervous activity and does not affect the behavior of horses of a strong, balanced, mobile type during participation in demonstrative performances and competitions. The results of the conducted researches allow: to improve the training system for horses of a strong balanced inert and severe unbalanced types of higher nervous activity at different periods of horses training in order to increase their stress resistance in conditions of competitive activity; to conduct a more qualitative selection of the best animals in breeding by the main selection criterion – ability to work; to receive more competitive horses for participation in National and International competitions for classical equestrian sport, which will increase the level of implementation of horses, price indices and the economic efficiency of the work of breeding farms in general.